PROSEDUR PENGGAJIAN DAN PEMBAYARAN TPP PADA BADAN PENDAPATAN DAERAH PEMERINTAH PROVINSI KALIMANTAN UTARA - Nunung Sri Nurhayati (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
This is a review of the salary and payment procedures of the Officer's Income Allowance (TPP) in the Regional Revenue Agency of the Government of Northern Kalimantan Province. The Regional Revenue Agency has the primary responsibility in managing the local income and tax receipts. Ensuring efficiency in the remuneration and payment process of the TPP is crucial to ensuring that every employee receives benefits in accordance with the policy in force. It not only increases staff satisfaction but also strengthens transparency and accountability within the organization. The study highlights concrete steps in the process, including data collection, TPP calculation based on established criteria, verification of claims, and delivery of payments to eligible staff. With a thorough understanding of these procedures, the Regional Revenue Agency can improve transparency, accountability, and staff satisfaction related to TPP management.